2021
DOI: 10.1177/15266028211031924
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report: Is the Lack of Sufficient Radial Force Unfreezing the “Frozen Elephant Trunk”?

Abstract: The “frozen elephant trunk” is a hybrid technique to treat aortic arch and proximal descending aortic pathologies in a single step. Despite its encouraging early and long-term results, some stent-graft-related adverse events have been reported. Here, we describe a possible treatment option to “re-freeze” the FET in case of loss of landing zone. We report a patient who developed significant kinking of the FET over the course of the first 2 postoperative years. The 1-year follow-up computed tomography angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, the association between stent graft kinking and aortic reintervention was not statistically significant ( p = 1.00) ( 12 ). Additionally, Öz et al ( 25 ) reported one case of kinking of this prosthesis post-FET. Here, the patient's 2- and 2.5-year follow-up CTA revealed graft kinking with proximal migration of the endograft portion of the FET, resulting in new thrombus formation, thus necessitating endovascular reintervention which was performed successfully.…”
Section: Incidencementioning
confidence: 95%
See 4 more Smart Citations
“…However, the association between stent graft kinking and aortic reintervention was not statistically significant ( p = 1.00) ( 12 ). Additionally, Öz et al ( 25 ) reported one case of kinking of this prosthesis post-FET. Here, the patient's 2- and 2.5-year follow-up CTA revealed graft kinking with proximal migration of the endograft portion of the FET, resulting in new thrombus formation, thus necessitating endovascular reintervention which was performed successfully.…”
Section: Incidencementioning
confidence: 95%
“…It is thought that the curvature of the prosthesis, in combination with the low radial force within the aorta may cause proximal migration and subsequent kinking of the stent. Hence, in an attempt to counteract the vector forces causing the kinking, longitudinal support, in the form of interrupted interconnecting wires, has also been suggested in the literature ( 25 , 35 ).…”
Section: Mechanismmentioning
confidence: 99%
See 3 more Smart Citations